More than a monologue. sexual diversity and the catholic church - Hinze, Christine Firer; J. Hornbeck, Patrick II (Catholic practice in North America., 2014)
The Second Vatican Council's landmark document Gaudium et spes called Catholics to cultivate robust, mutually enriching dialogue with the modern world by attentively and discerningly listening to the ""voices of our times."" This distinctive new publication, the first of two volumes that explore sexual diversity and the Catholic Church, gathers an important set of these voices: the testimonies and reflections of Catholic and former Catholic LGBTQ (lesbian, gay, bisexual, transgender, and queer) persons, their friends, family members, and those who teach and accompany them. Drawn from a series.